(untitled) (Studi di storia medioevale e di diplomatica - Nuova Serie, 2022)
The volume is one of the results of the PRIN 2015, Alle origini del welfare (XIII- XVI secolo). Radici medievali e moderne della cultura europea dell’assistenza e delle forme di protezione sociale e credito solidale, principal investigator Gabriella Piccinni. The authors approach the history of mountain hospitals in a comparative perspective, focusing on case studies from Northern and Central Italy, Southern France, and Northern Spain. Archival and orographic research on a hitherto little‐explored theme of medieval hospitals’ history has made it possible to redefine the physiognomy of mountain hospitals – which turned out to be not only hospices and refuges, but also sanctuaries, fortresses, farms, and inns – and to revise some historiographic convictions: the functionality of these institutions appeared to depend more on the needs of those who lived, worked, and con‐ trolled mountain areas, rather than on the needs of occasional travellers, such as pilgrims. The book is therefore an original and significant contribution to the reconstruction of the historical landscapes and of the economic, political and social structures, as well as the cultural and religious frameworks, of the me‐ dieval territories.